(Imidazol‐2‐yl)methyl‐1, 3‐propanediones: Regioselective C–H Functionalization of the Imidazole Ring by Acylacetylene/Aldehyde Pairs. Issue 6 (1st February 2016) - Trofimov, Boris A.; Andriyankova, Ludmila V.; Nikitina, Lina P.; Belyaeva, Kseniya V.; Mal'kina, Anastasiya G.; Bagryanskaya, Irina Yu.; Afonin, Andrei V.; Ushakov, Igor A.
Abstract: The metal‐free regioselective C‐2–H functionalization of 1‐substituted imidazoles has been effected by a cascade reaction with aromatic or heteroaromatic aldehydes and acylacetylenes under mild conditions (55–60 °C, MeCN) to give (imidazol‐2‐yl)methyl‐1, 3‐propanediones in 22–77 %, mainly 40–70 % yields. Abstract : 1‐Substituted imidazoles, acylacetylenes, and aldehydes undergo a facile and regioselective cascade reaction under metal‐free conditions to give (imidazol‐2‐yl)methyl‐1, 3‐propanediones through C‐2–H functionalization. These reactive building blocks and drug precursors, which have previously been inaccessible, are now readily available by the developed reaction.